Aesthetic awareness and its relationship to skill performance among students of the Department of Art Education (Al-Academy, 2025)
The current study addressed the relationship between aesthetic awareness and skill performance. The problem of the current research was summarized in the following questions: What is the level of aesthetic awareness possessed by students of the Department of Art Education?- Is skill performance different for students with a high level of aesthetic awareness than for students with a low level of aesthetic awareness?- Is there a relationship between aesthetic awareness and skill performance among students of the Art Education Department?The goal of the research was to reveal aesthetic awareness and its relationship to skill performance among students of the Art Education Department. The first chapter also presented an introduction to the limits of the research and defined the terms that define them. As for the second chapter, which is represented by the theoretical framework, it includes two sections: the first: aesthetic awareness and the theories that explain it. The second section: represents the skill disease and its patterns. The third chapter includes the research, While the fourth chapter included the results of the research, conclusions, recommendations and proposals, the researchers reached a number of results, including: the availability of an acceptable level of aesthetic awareness among students. It can be noted that the arithmetic averages for the gender variable and the total grade are very close, which indicates that there is a convergence between the levels of the total sample, and the reason is due to This enables students to respond quickly to stimuli, in addition to the cultural and cognitive diversity enjoyed by university students, which in turn influenced the results of the study.